Multimodal imaging findings in 'hyper-early' stage MEWDS. Issue 10 (15th February 2017) - Cahuzac, Armelle; Wolff, Benjamin; Mathis, Thibaud; Errera, Marie-Hélène; Sahel, José-Alain; Mauget-Faÿsse, Martine
Abstract : Objective: To describe a new stage of multiple evanescent white dot syndrome (MEWDS), occurring at a very early phase of the disease. Methods: Retrospective analysis of clinical, angiographic and tomographic findings in four patients with 'hyper-early' stage MEWDS. Results: In four patients seen within 1 week of the onset of symptoms, fundus analysis revealed macular granity and the classic yellow–white dots, some having no corresponding hyperautofluorescent pattern. Spectral-domain optical coherence tomography (SD-OCT) showed central foveal disruption of the ellipsoid zone (EZ) and interdigitation layer with a hyper-reflective dome-shaped lesion. In two patients, fluorescein angiography (FA) revealed an intermediate hypofluorescent perimacular halo, whereas late indocyanine green angiography (ICGA) showed a hyperfluorescent halo as well as the classic MEWDS features. After a few days, the EZ disruption appeared complete on OCT and fundus autofluorescence (FAF) in all patients. Visual acuity, OCT and FAF findings had fully recovered within 3 months. Conclusions: We have shown a new feature of MEWDS on FAF, OCT, FA and ICGA, corresponding to a very early stage of the disease.